Grammatical Metaphora In Novel Daddy Long Legs - Ramadhan Pambudi (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2023)
This study deals with Grammatical Metaphor in Novel Daddy Long Legs. The objectives of the study is to investigate out the forms of grammatical metaphor used in novel Daddy Long Legs and to investigate out the dominant types of grammatical metaphor in novel Daddy Long Legs? In this research, the researcher was applied the qualitative research method to analyze the data. The source of in this research was teken from novel Daddy Long Legs. The researcher chooses this novel because is interesting to research and this novel most poppular in seoul. Beside that, the researcher believes that the grammatical metaphor always used in senteces of novel especially in novel Daddy Long Legs. Having analyzed the use of grammatical metaphor in Novel Daddy Long Legs, conclusions are drawn as the following: There are some grammatical metaphors found in novel Daddy Long Legs. The types of grammatical metaphor that found in novel Daddy Long Legs are ideational metaphor and interpersonal metaphor. The most dominant grammatical metaphor used in Novel Daddy Long Legs is ideational metaphor (67,12%).